(3cJGH GdJGQjN aj eYQaI QhGI GdMOjK hfbdI GdBKGQ hGdSff hJejjR KbGJge ef VYaGFge hJGQjN haGJges - (3eMeO Hf ESeGYjd Hf EHQGgje Hf GdeZjQI GdHNGQj, CHh YHO Gddg,J (B256 (3g` s
(3ChdgG (B:s
(3HYO PcQ SfO QhGjI GdcJGH GdeNJUQ ef JGQjN gLQI QShd Gddg Udi Gddg Ydjg hSde hGdegGLQjf hGdCfUGQ hWHbGJ GdJGHYjf hef HYOge hef jZQH ai MOjKg s
(3ecJhHI Yf fSNI eSehYI SfI (B424(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B120 s
(3eUOQ GbJfGA GdCUd (B:s
(3eOfjI (B(524) s
Keywords: (3GdJGQjNs